Asuhan Keperawatan Pada Ny. S dengan Post Operasi Sectio Caesarea Indikasi Fetal Distres di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Khofidatun Rofiah; Tati Karyawati; Siti Fatimah (Lembaga Pengembangan Kinerja Dosen, 2024)
Caesarean section (CS) delivery is a surgical process to deliver a fetus through an incision in the abdominal wall and uterine wall. The purpose of this paper is to determine and provide nursing care for Mrs. Swith post-operative cesarean section indications of fetal distress in the Nusa Indah ward of dr. Soeselo hospital, Tegal Regency in accordance with nursing standards. The method used is descriptive with a case study approach. The data collection tchniques in this scientific paper are in the form of interviews, observations, documentation studies and literature studies. From the case review, it was found that the client’s main complaint was pain in the surgical stitches, P: pain when moving, Q: pain like being pressed, R: pain in the surgical stitches, S: scale 5, T: intermittent. The nursing problems found were acute pain, impaired skin/tissue integrity and knowledge deficit. Interventions were arranged based on the theory in DKI, SLKI and SIKI as well as on the client’s condition and could be implemented.